ĐÁH\NH GIÁ MỘT SỐ PHƯƠNG PHÁP NÔI SUY DỊ THƯỜNG ĐỘ CAO TRÊN MÔ HÌNH - Lân, Phạm Hoàng; Luyên, Bùi Khắc (Vietnam Journal of Earth Sciences, 2017)
Based on 3 mathematical models, the paper considers height anomaly interrpolation by using Polynomial method with 6 and 10 parameters, Spline, Kriging and Collocation methods. The computation data show that the Collocation method provides best result of interpolation. So for the interpolation distance shorter than 5 km, this method gives the accuracy of no more than 0.01 m. For the distance shorter than 10 km - no more than0.10 m, and for the distance shorter than 15 km -no more than 0.3 m.